2004
DOI: 10.1111/j.1447-0756.2004.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting endometrial cancer in patients with a preoperative diagnosis of atypical endometrial hyperplasia

Abstract: A relatively high incidence of EC is seen in patients with a diagnosis of AEH. Diagnostic results of pipelle biopsy and curettage were comparable. Frozen sections of hysterectomy specimens does not guarantee to exclude the possibility of EC, especially in patients with no myometrial invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…These results are similar to those in previous reports (Table 5) (Kurman and Norris 1982;Janicek and Rosenshein 1994;Lambert et al 1994;Hunter et al 1994;Liapis et al 1994;Widra et al 1995;Dunton et al 1996;Xie et al 2002;Agostini et al 2002;Kimura et al 2003;Bilgin et al 2004;Shutter and Wright 2005;Merisio et al 2005;Garuti et al 2006;Trimble et al 2006;Dordević et al 2007). Sampling errors Values are shown as a mean (± s.d.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to those in previous reports (Table 5) (Kurman and Norris 1982;Janicek and Rosenshein 1994;Lambert et al 1994;Hunter et al 1994;Liapis et al 1994;Widra et al 1995;Dunton et al 1996;Xie et al 2002;Agostini et al 2002;Kimura et al 2003;Bilgin et al 2004;Shutter and Wright 2005;Merisio et al 2005;Garuti et al 2006;Trimble et al 2006;Dordević et al 2007). Sampling errors Values are shown as a mean (± s.d.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature studies about the accuracy of FS are limited. Some studies reported low accuracy rate of FS (Bilgin et al, 2004;Indermaur et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is typically diagnosed by endometrial biopsy or curettage when a woman is noted as suffering from abnormal uterine bleeding particularly in older women. Endometrial hyperplasia is classified into 4 different categories: simple hyperplasia with or without cytological atypia and complex hyperplasia with or without cytological atypia (Bilgin et al, 2004;Indermaur et al, 2007). Atypical endometrial hyperplasia has been strongly associated with endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen section analysis of hysterectomy specimens in patients with atypical endometrial hyperplasia was found to be necessary to determine the presence of cancer and the need for surgical staging in a different study (Gundem et al, 2003). Bilgin et al (2004) reported that frozen section has a low accuracy rate to excluding the possibility of endometrial cancer in patients with preoperative diagnosis of CAEH (Bilgin et al, 2004). In several studies, it was reported that the underlying adenocarcinoma rate was 47.8% in patients with a preoperative diagnosis of CAEH (Lambert et al, 1994;Valenzuela et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation